Evaluation of the effect of chrysophyllum cainito L. extract on BxPC-3 pancreatic cell glucose concentration using an ESP8266-based microcontroller near-infrared absorption spectroscopy system - Reganit, Pauline Anne P. (Animo Repository, 2024)
This study explored the effect of Chrysophyllum cainito L. on the glucose concentration of BxPC-3 human pancreatic cancer cells using non-invasive near-infrared spectroscopy integrated with an ESP8266 microcontroller as a glucose monitoring device. The objective of the study is to validate the anti-diabetic property of C.cainito extract by measuring the glucose levels of BxPC-3 using the device and comparing its accuracy with commercial glucometers. The created ESP8266 glucometer utilized a 940 nm NIR LED, and a photodiode. Gmate® Control Solution was used to obtain the reference glucose values, for glucose concentration basis of the True Metrix Control Solution, using the Accu Chek glucometer, and a standard curve using the True Metrix Control Solution was used for the conversion of voltage to glucose concentration using the ESP8266 glucometer. The main analyte of the study was cDMEM media from the T-Flasks containing BxPC-3 cells that had a total of 12 samples, 3 control and 9 experimental. IC10, 63 µg/mL, was used to treat the experimental groups and a treatment period of 18 hours was implemented. Results show that the ESP8266 glucometer had a mixture of results in the T - test in terms of precision, but was deemed to be medically accurate using the Clarke Error Grid Analysis. Results also indicate that although the cainito fruit extract provided antidiabetic properties, the difference in glucose concentration between the control and experimental groups was not significant when measured using the commercial glucometer but was significant for the ESP8266 glucometer.